METACOGNITION IN ENTREPRENEURS: PSYCHOMETRIC DIAGNOSTIC ASSOCIATED TO AGE AND SEX - Lima Filho, Raimundo Nonato; Bruni, Adriano Leal (Revista Eletrônica de Administração, 2017)
The aim of this study was to identify elements that show the influence of the age and sex variables in the metacognitive level of professionals. Survey participants were 851 professionals registered in Bahia's Regional Administration Council who own their own businesses. Two validated psychometric instruments were used: Metacognitive Awareness Inventory (MAI) and the Metacognitive Activities Inventory (MCA-I). The hypothesis held that the respondent's age and sex influence their Metacognitive Profile. From the Structural Equation Modeling, the results indicate that the sex variable showed no significant relationship to the Metacognitive Profile. The implications of this study provide empirical conclusions that can aid entrepreneurs, companies, higher education institutions to understand the metacognitive aspects that influence the entrepreneurs behavior more systematically. Empirically, these results contribute so that the participating drivers of this study, as they develop metacognitive aspects, acquire a competitive advantage in their entrepreneurial performance.